Determinants Of Organizational Transformation, Corporate Culture, On Corporate Performance Mediated By Organizational Citizenship Behavior At PT. Angkasa Pura Aviasi - Budi Karyono, Aris; Yuliantini, Yuliantini; Agusinta, Lira; Setyawati, Aswanti; Tatiana, Yana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to identify and analyze the determinants of Organizational Transformation and Corporate Culture on Corporate Performance with Organizational Citizenship Behavior as an intervening variable at PT Angkasa Pura Aviasi. The sample in this study was determined using the Slovin formula, resulting in a total of 232 employees of PT Angkasa Pura Aviasi as respondents. Data collection techniques used in this study included questionnaires and interviews, while the research approach was quantitative and employing SEM-PLS statistical analysis. The data was processed using SmartPLS 3.3.3 software. The results of the study demonstrate that Organizational Transformation has a direct positive and significant effect on Corporate Performance with a path coefficient value of 0.873, P-Values = 0.000, T-statistic = 32.568. Corporate Culture also has a direct positive and significant effect on Corporate Performance with a path coefficient value of 0.157, P-Values = 0.002, T-statistic = 2.935. The influence of Organizational Transformation on Organizational Citizenship Behavior shows a path coefficient value of 0.180, P-Values = 0.000, and T-statistic = 7.256. The influence of Corporate Culture on Organizational Citizenship Behavior has a path coefficient value of 0.157, P-Values = 0.000, and T-statistic = 3.6374. The influence of Organizational Transformation on Corporate Performance through Organizational Citizenship Behavior shows a path coefficient value of -0.009, P-Values = 0.248, and T-statistic = 0.681. The influence of Corporate Culture on Corporate Performance through Organizational Citizenship Behavior shows a path coefficient value of -0.042, P-Values = 0.236, and T-statistic = 0.721. Finally, the influence of Organizational Citizenship Behavior on Corporate Performance shows a path coefficient value of -0.052, P-Values = 0.235, and T-statistic = 0.722. Keywords: Organizational Transformation, Corporate Culture, Organizational Citizenship Behavior, Corporate Performance.